Normative Control of Law as the Basic Power of Constitutional Court - Polovchenko, Konstantin A. (Opción, 2019)
The article presents an analysis of the leading activity of the Constitutional Court of Serbia –via the general scientific method of ascent from the abstract to the concrete. As a result, the proceedings in the Constitutional Court of Serbia on cases of preventive control of the constitutionality of a law adopted by the National Assembly. In conclusion, the author comes to the conclusion that scope of authority related to the normative control is one of the most extensive, and the constitutional normative regulation in Serbia is one of the most detailed in Central and Eastern Europe.